Analisis Proses Bisnis PPSDM MIGAS Menggunakan Framework CIMOSA - Fachrizal Edyansyah (Swara Patra, 2023)
As the organizing body for human resource development, as well as being the only center for human resource development for the oil and gas sub-sector industry, PPSDM MIGAS hopes to be able to improve the competence of oil and gas workers in Indonesia. In this process it is necessary to have knowledge related to the business processes that are carried out so that the process and direction to be achieved can be seen to develop human resources in the oil and gas sector. The purpose of this study is to obtain an overview of the business processes carried out by PPSDM MIGAS. In this study, the computer integrated manufacturing for pen system architecture (CIMOSA) framework is used as an approach to find out the details of business processes. The research methodology is carried out by means of observation and descriptive studies. From the results of this study, detailed information on each business process in PPSDM MIGAS has been obtained. Starting from managing processes, core business processes, to support processes, all have been carried out by PPSDM MIGAS. Overall, from the analysis of the PPSDM MIGAS business process mapping using the CIMOSA framework, it can be said that the existing business processes are clear and well directed. It is hoped that in the future PPSDM MIGAS can continue to develop services in order to produce superior and competitive human resources in the oil and gas sector.